Thermodynamic analysis of a variable viscosity reactive hydromagnetic couette flow within parallel plates - Hassan, Anthony R; Lawal, Olufemi W; Amurawaye, Funmilayo F (Tanzania Journal of Science, 2021)
This investigation is to consider the impact of a temperature-dependent variable viscosity of a reactive hydromagnetic Couette fluid flowing within parallel plates. The variable property of the fluid viscosity is thought to be an exponential relation of temperature under the impact of magnetic strength. The differential equations controlling the smooth movement of fluid and energy transfer are modeled and solved by using the series solution of modified Adomian decomposition technique (mADM). The outcomes are shown in tables and graphs for different estimations of thermophysical properties present in the flow regime together with the rate of entropy generation and irreversibility distribution outcome. Keywords: Reactive fluids, Couette Flow, variable viscosity, hydromagnetic and modified Adomian decomposition method (mADM).